Phenotypic Plasticity & Evolution: Causes, Consequences, Controversies David W. Pfennig (ed). xxxi + 404 pp., index. Evolutionary Cell Biology. Boca Raton, FL: CRC Press, Taylor & Francis Group, 2021. 230 (hardback); Open Access (pdf). Issue 6 (18th October 2022) - Love, Alan C.; Wagner, Günter P.
Highlights: Details the important contributions and significance of this edited volume for the field. Describes key conceptual questions that remain outstanding.